2013
DOI: 10.1111/aos.12125
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and intraocular pressure – results from a case –control and an intervention study

Abstract: ABSTRACT.Purpose: To study the associations between serum 25-hydroxy-vitamin D (25(OH)D) levels, vitamin D administration and intraocular pressure (IOP). Methods: The design of the study included a nested case-control study and a randomized controlled intervention trial. In the first part, healthy Caucasians with high or low serum 25(OH)D levels were recruited from a populationbased study. IOP of the right eye was measured by the use of a rebound tonometer. In the second part, those with low serum 25(OH)D leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 15 publications
2
37
1
2
Order By: Relevance
“…In an animal study, vitamin D eye drops in nonhuman-primates resulted in a reduction of intraocular pressure by 20%, mainly by increasing the uveoscleral outflow [8]. On the opposite, a randomized controlled intervention trial involving humans found no IOP reduction after high-dose vitamin D3 supplementation (20,000 IU twice per week) during 6 months [20]. In our study, POAG cases were exhibiting lower IOP compared to controls (Table 1), probably due to appropriate POAG treatments (the vitamin D supplementation being similar in both groups).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In an animal study, vitamin D eye drops in nonhuman-primates resulted in a reduction of intraocular pressure by 20%, mainly by increasing the uveoscleral outflow [8]. On the opposite, a randomized controlled intervention trial involving humans found no IOP reduction after high-dose vitamin D3 supplementation (20,000 IU twice per week) during 6 months [20]. In our study, POAG cases were exhibiting lower IOP compared to controls (Table 1), probably due to appropriate POAG treatments (the vitamin D supplementation being similar in both groups).…”
Section: Discussionmentioning
confidence: 97%
“…(i) Vitamin D may play a role in the regulation of the intraocular pressure [20]. In an animal study, vitamin D eye drops in nonhuman-primates resulted in a reduction of intraocular pressure by 20%, mainly by increasing the uveoscleral outflow [8].…”
Section: Discussionmentioning
confidence: 99%
“…В последние годы появились единичные подтверждения участия дефицита витамина D в развитии как первичной открыто-угольной глаукомы (ПОУГ), так и псевдоэксфо-лиативного синдрома (ПЭС) [16,24,25]. Возмож-но, это связано с наличием иммуносупрессивной активности витамина D, а также с его участием в регуляции процессов клеточной пролиферации, дифференцировки и апоптоза, в том числе в глаз-ной нейроглии [8,14,19].…”
Section: Introductionunclassified
“…A study of the impact of vitamin D supplements on the eye's intraocular pressure (IOP) reported no differences before and after treatment (Krefting et al, 2013). Other key studies discussing the association between vitamin D and ocular health in both humans and animal models are summarised in Table 2-1 and 2-2.…”
Section: Vitamin D and Ocular Healthmentioning
confidence: 99%
“…There is one reported human study on the impact of vitamin D supplements on the eye's IOP, stating that vitamin D had no significant effects (Krefting et al, 2013).…”
Section: Intraocular Pressure (Iop)mentioning
confidence: 99%